"Från vaktmästare till psykolog." : En kvalitativ studie om kvinnors psykosociala arbetsmiljö och känsloarbete inom äldreomsorgen - Johansson, Anette (2011)
This paper in sociology is about psychosocial work environment and how women that work in elderly care experiences their work situation. The purpose of this study is to describe women's perceived stress and their emotional work in elderly care in Piteå. The chosen method for this paper is a qualitative method with six semi structured interviews with informants that work in elderly care. The theoretical reference is based on Karasek and Theorells demands- control and support model, witch is about how different characteristics in work gives different starting points for individual’s health. The results showed that the employees felt that they have a good working situation and that they were satisfied with their colleagues and managers. Furthermore, results showed that employees did not think they had too high demands for themselves and that the support at their workplace was good, however, they expressed that they felt that they couldn’t control their work. Validerat; 20110702 (anonymous)